a IMPLEMENTASI SISTEM KENDALI PEMICU LEDAKAN DETONATOR BERBASIS SMART RELAY GUNA MENDUKUNG DISPOSAL MUNISI: SISTEM KENDALI PEMICU LEDAKAN DETONATOR - Ahmad, Wira; widiatmoko, dekki (Pustaka Poltekad, 2024)
In the process of munitions disposal, there are sometimes challenges that can pose risks to personnel or damage equipment. To address this, a smart relay system was developed with the aim of creating and testing a detonation control system to support munitions disposal in military operations. This research used an experimental approach, where the system was tested at various distances and environmental conditions. The testing aimed to measure response speed, relay activation success rate, and signal range. The results showed that the **smart relay** system was capable of operating with a fast response time up to a distance of 250 meters, with a success rate of 98% in the laboratory and 96% in outdoor conditions. However, the system still faces challenges in terms of signal range and battery life, especially at distances over 400 meters or in extreme environmental conditions. In conclusion, this control system is effective and efficient in enhancing the safety of munitions disposal. However, further development is needed to extend the signal range and optimize battery life. It is recommended to integrate stronger communication technology and more efficient batteries to improve the system's stability and performance in the field. Keywords: Control system, Smart Relay, ammunition disposal, signal range